2007
DOI: 10.1111/j.1365-2672.2006.03221.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial synthesis of poly(hydroxybutyrate- co-hydroxyvalerate) using carbohydrate-rich mahua (Madhuca sp.) flowers

Abstract: Aims:  The objective of the present work was to utilize an unrefined natural substrate namely mahua (Madhuca sp.) flowers, as a carbon source for the production of bacterial polyhydroxyalkanoate (PHA) copolymer by Bacillus sp‐256. Methods and Results:  In the present work, three bacterial strains were tested for PHA production on mahua flower extract (to impart 20 g l−1 sugar) amongst which, Bacillus sp‐256 produced higher concentration of PHA in its biomass (51%) compared with Rhizobium meliloti (31%) or Sphi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…This is a signiWcant result because there have been only a few reports of P (3HB-co-3HV) synthesis from a single carbon source [22]. Composition of the carbon substrate used for fermentation and utilization of appropriate bacterial strain control the production of copolymers of PHB [23]. When tested in combination with propionic acid, the precursor for 3HV copolymer accumulation, at a concentration of 2 ml/l, Bacillus sp.…”
Section: Discussionmentioning
confidence: 87%
“…This is a signiWcant result because there have been only a few reports of P (3HB-co-3HV) synthesis from a single carbon source [22]. Composition of the carbon substrate used for fermentation and utilization of appropriate bacterial strain control the production of copolymers of PHB [23]. When tested in combination with propionic acid, the precursor for 3HV copolymer accumulation, at a concentration of 2 ml/l, Bacillus sp.…”
Section: Discussionmentioning
confidence: 87%
“…However, PHB does not possess material properties because of its crystalline and brittle nature. The co-polymer containing both PHB and PHV (poly-b-hydroxyvalerate) is more flexible and tougher and of greater industrial interest and can be obtained by the co-feeding propionate and pentonoate (Anil-Kumar et al 2007;Full et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Reports suggesting the use of Bacillus for the production of a range of different PHAs by utilizing different carbon sources are known. These include incorporation of the tercopolymer of 3HB, HV, and 3HHX (3-hydroxy-hexanoate) utilizing b-caprolactone (Labuzek and Radecka 2001), P(3HB-co-3HV) from different carbon sources (Tajima et al 2003), PHB co-PHV in mahua flowers (Anil-Kumar et al 2007), from sucrose (Shamala et al 2003), and PHBs from soy molasses oligosaccharides (Full et al 2006), sugarcane molasses, and corn steep liquor (Gouda et al 2001). The co-polymer synthesis from structurally unrelated carbon sources suggests that Bacillus has the potential for production of a new PHA co-polymer using different substrates (Valappil et al 2007b).…”
Section: Introductionmentioning
confidence: 99%
“…One of the limiting factors for the economic production of PHAs is the cost of feedstock, which contributes up to 40% of the total operating costs [2]. Several successful studies have been reported on PHA production from cheap and renewable carbon sources, for example, date syrup, mahua flowers, and palm oil mill effluent (POME) [35]. Ntaikou et al [6] reported that combined biohydrogen and biopolymers were produced from olive oil mill wastewater by two-stage reactor system with poly-3-hydroxybutyrate, P(3HB) yield of 8.94% per dry biomass weight.…”
Section: Introductionmentioning
confidence: 99%